1996
DOI: 10.1002/anie.199623531
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Hydroxylation by H2O2 and O2 Catalyzed by a μ‐Oxo Diiron(III) Complex

Abstract: An excellent functionalized enzyme model for the active site of methane monooxygenase and ribonucleotide reductase is represented by the μ‐ace‐tato‐ and μ‐oxo‐bridged diiron complex 1. Reaction with H2O2 or O2 in the presence of ascorbate leads to hydroxylation of one phenyl ring to a phenol. This then coordindates to the metal center with formation of a mononuclear complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…185 Intramolecular ortho-hydroxylation is observed after addition of tBHP and mechanistic investigations revealed that these systems are potent functional models, which support a better understanding of the enzymes' reactivity. [185][186][187] …”
Section: Iron Nonheme Complexes Bearing Pure N-donor Ligandsmentioning
confidence: 99%
“…185 Intramolecular ortho-hydroxylation is observed after addition of tBHP and mechanistic investigations revealed that these systems are potent functional models, which support a better understanding of the enzymes' reactivity. [185][186][187] …”
Section: Iron Nonheme Complexes Bearing Pure N-donor Ligandsmentioning
confidence: 99%
“…66 Interestingly, several diiron(III) complexes catalyzes intra-molecular aliphatic 67 and aromatic oxidation reactions, where the phenyl group is usually oxidized using various oxidants. [68][69][70][71][72] Although, various m-oxo-bridged nonheme diiron(III) complexes that mimic the functions of diiron enzymes have been reported earlier, the design and study of diiron(III) complexes would enhance the understanding further to utilize the complexes as excellent catalysts for the oxidation of organic substrates, particularly for alkane functionalization and alkene epoxidation reactions. Moreover, the factors determining the selectivity as well as efficiency of the catalysts remain still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aromatic hydroxylation mediated by oxo-bridged diiron(III) complexes is sparsely reported in the literature. 10,21 The oxo-bridged diiron(III) complex based on an EDTA based ligand has been shown to hydroxylate the coordinated phenyl ring. 21 However, the diferric complex was found to disintegrate into a mononuclear(III) product at the end of the reaction.…”
Section: Mechanistic Aspects Of Aromatic Hydroxylationmentioning
confidence: 99%
“…10,21 The oxo-bridged diiron(III) complex based on an EDTA based ligand has been shown to hydroxylate the coordinated phenyl ring. 21 However, the diferric complex was found to disintegrate into a mononuclear(III) product at the end of the reaction. Very recently, Wang et al…”
Section: Mechanistic Aspects Of Aromatic Hydroxylationmentioning
confidence: 99%